Implementation of a marketing plan for the dissemination of the WHO SkinNTDs app in Cameroon - Henri Claude Moungui; Paul Tonkoung Iyawa; Hugues Nana-Djeunga; Jose Antonio Ruiz-Postigo; Carme Carrion (PLoS ONE, 2025)
Background Skin-related neglected tropical diseases (sNTDs) remain a significant public health challenge in Cameroon, where limited resources, training, and infrastructure hinder early diagnosis and management. The World Health Organization (WHO) has developed the SkinNTDs app version 3.0 as a digital solution to assist frontline healthcare workers (FHWs) in recognizing and managing sNTDs. As utilization will rely on a high degree of awareness among FHWs, a dedicated and effective marketing plan is required. This study describes the design, implementation, and evaluation of a structured marketing plan to promote the app among FHWs in Cameroon. Methods We conducted a pilot quasi‑experimental before‑and‑after study comparing three 6‑month phases—pre‑campaign, campaign, and post‑campaign. The multi‑channel marketing campaign combined communications via WhatsApp, in‑person training sessions, video presentations, and email outreach. Google Play Console Analytics provided monthly metrics on store listing visits, downloads, installations, uninstalls, and retention. Results During the campaign (1 April 2024–30 September 2024), store page visits totaled 961, yielding 616 downloads (conversion rate = 64.1%) and the app was installed 751 times; new-user acquisition exceeded 81.6%. Net installs surged by 227.3% in April and 140.4% in May, with retention above 88%. ANOVA revealed significant period effects on growth rate (p = 0.007, ε² = 0.591), loss rate (p = 0.011, η² = 0.452), churn rate (p = 0.003, η² = 0.532), and retention rate (p = 0.003, η² = 0.532), with campaign performance superior to pre‑ and post‑campaign phases. Interrupted time series analyses found gradual adoption and sustained retention following intervention start, but significant decrease at campaign end. Conclusion A context‑adapted, multi‑channel marketing strategy markedly improved adoption and retention of the WHO SkinNTDs app among Cameroonian FHWs. Digital (WhatsApp, videos) and face‑to‑face (training) channels were complementary. Sustained integration into routine health activities and automated re‑engagement tools are recommended to maintain long‑term use and inform scale‑up in other endemic settings.